Posttransplantation lymphoproliferative disorder after pediatric solid organ transplantation: experiences of 20 years in a single center - Hyung Joo Jeong; Yo Han Ahn; Eujin Park; Youngrok Choi; Nam-Joon Yi; Jae Sung Ko; Sang Il Min; Jong Won Ha; Il-Soo Ha; Hae Il Cheong; Hee Gyung Kang (Korean Pediatric Society, 2017)
PurposeTo evaluate the clinical spectrum of posttransplantation lymphoproliferative disorder (PTLD) after solid organ transplantation (SOT) in children.MethodsWe retrospectively reviewed the medical records of 18 patients with PTLD who underwent liver (LT) or kidney transplantation (KT) between January 1995 and December 2014 in Seoul National University Children's Hospital.ResultsEighteen patients (3.9% of pediatric SOTs; LT:KT, 11:7; male to female, 9:9) were diagnosed as having PTLD over the last 2 decades (4.8% for LT and 2.9% for KT). PTLD usually presented with fever or gastrointestinal symptoms in a median period of 7 months after SOT. Eight cases had malignant lesions, and all the patients except one had evidence of Epstein-Barr virus (EBV) involvement, assessed by using in situ hybridization of tumor tissue or EBV viral load quantitation of blood. Remission was achieved in all patients with reduction of immunosuppression and/or rituximab therapy or chemotherapy, although 1 patient had allograft kidney loss and another died from complications of chemotherapy. The first case of PTLD was encountered after the introduction of tacrolimus for pediatric SOT in 2003. The recent increase in PTLD incidence in KT coincided with modification of clinical practice since 2012 to increase the tacrolimus trough level.ConclusionWhile the outcome was favorable in that all patients achieved complete remission, some patients still had allograft loss or mortality. To prevent PTLD and improve its outcome, monitoring for EBV infection is essential, which would lead to appropriate modification of immunosuppression and enhanced surveillance for PTLD.